KONSEP NUSYUZ MENURUT SYEKH NAWAWI AL-BANTANI DAN MUHAMMAD SYAHRUR - Fajar Mukti Amirullah; Yoyo Hambali; Baiduri Baiduri (MASLAHAH (Jurnal Hukum Islam dan Perbankan Syariah), 2022)
This study examines the public’s lack of understanding of the NUSYUZ concept, which still means discrimination against one gender only. Scholars also interpret it not only to punish one party. However, there are still many who understand that NUSYUZ is an act of a wife who disobeys her husband, it could also be a husband who is NUSYUZ against his wife, and here the author wants to examine the lack of understanding of NUSYUZ which is still discrimination from gender issues. The purpose of this study is to eliminate gender discrimination from the concept of NUSYUZ that exists in the wider community, there are none other than wives who are NUSYUZ against their husbands and husbands who are NUSYUZ against their wives. In this study using the Library Research method or library research, by reading and dissecting books and previous studies in order to find the problem of gender deviations that occur in the NUSYUZ concept. The results of this study state that the concept of Nusyuz according to Sheikh Nawawi Al-Bantani that it is permissible to reprimand with physical touch as long as it does not cause injury, Muhammad Syahrur’s concept makes women honor. While the content discussed is gender equality and eliminating discrimination against men and women, the benefits resulting from the loss of discrimination make everyone bear the same burden between the relationships of men and women who are already married.